2005
DOI: 10.1158/0008-5472.can-05-0581
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Replication Ability of E1-Deleted Adenoviruses Correlates with Increased Brain Tumor Malignancy

Abstract: E1 region replacement adenoviruses are replication defective and are propagated in cells providing adenovirus E1A and E1B proteins. Although they are being developed for antitumor therapies, the proliferative behaviors of these viruses in normal brain tissues or in brain tumors are unknown. To address this, freshly cultured cells from normal human brain and common brain tumors (astrocytomas and meningiomas) were infected using wild-type species C adenoviruses and adenoviruses missing E1A (H5dl312) or E1A plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…Although these AdVs use cancer-specific promoters, the adenoviruses replicate in the target cells and produce damaging effects through adenovirus gene expression in the target and surrounding cells. Although it has been reported that replication of E1-dereted AdV can be detected by Southern hybridization technique in HeLa cells at a higher MOI (42) and in other certain cells two weeks after infection (43), the replication level seemed too low to influence on the results described here.…”
Section: Discussioncontrasting
confidence: 58%
“…Although these AdVs use cancer-specific promoters, the adenoviruses replicate in the target cells and produce damaging effects through adenovirus gene expression in the target and surrounding cells. Although it has been reported that replication of E1-dereted AdV can be detected by Southern hybridization technique in HeLa cells at a higher MOI (42) and in other certain cells two weeks after infection (43), the replication level seemed too low to influence on the results described here.…”
Section: Discussioncontrasting
confidence: 58%
“…Second, the PSMA aptamer—that is selected to bind to a particular transmembrane protein overexpressed in prostate cancer cells [ 26 ] —enables cell targeting and efficient internalization of the cargos through an endocytic pathway. [ 27,28 ] Finally, there is a growing number of studies showing that cholesterol‐anchored nanostructures can reversibly associate with and laterally diffuse on lipid bilayers of the plasma membrane. [ 29 ] Given this, we speculated that the decoration of DNF with hydrophobic cholesterol [ 30 ] would mimic the amphiphilic nature of the cell membrane, [ 29,31 ] leading to a synergistic effect in cellular uptake together with the receptor‐binding aptamers.…”
Section: Figurementioning
confidence: 99%
“…Thus, the development of novel and improved therapeutic approaches is necessary. Adenoviruses-mediated gene therapy strategies have been proposed and studied in clinical trials; however, results with traditional adenovirus serotype 5 (Ad5)-based vectors have been disappointing (13)(14)(15)(16). A significant reason for the disappointing outcome with Ad5-based vectors is likely the low expression of the coxsackievirus and adenovirus receptor (CAR) on GBM cells.…”
Section: Introductionmentioning
confidence: 99%